The usage of highly absorbent antimicrobial polyurethane foam in wound management of pyomyositis - Mor Japar Khan, Ed Simor Khan; Chin, Yen Lee; VA Abraham, Jacob; N., Premchandran (OmniaMed Communications Ltd., 2019)
Intra-muscular abscess is a suppurative infection involving the skeletal muscle. Operative management remains the mainstay together with timely administration of systemic antibiotics. Timely usage of antimicrobial dressings assists the wound bed preparation for secondary closure.